Evaluating the effect of sports compression tights on balance, sprinting, jumping and change of direction tasks. - Leabeater, Alana; Vickery-Howe, Danielle; Perrett, Corey; James, Lachlan; Middleton, Kane; Driller, Matthew (Sports Biomechanics, 2025)
Compression garments are commonly used during athletic tasks. However, the effect of compression garments on balance, sprinting, jumping and change of direction performance requires further investigation. In the current study, 24 recreationally active participants (12 males, 12 females, age 27 ± 3 years) completed single-leg balance tasks, countermovement jumps, drop jumps, 10 m straight line sprints and change of direction tasks wearing either compression tights (COMP) or regular exercise tights (CON). There was a significant main effect of the condition for 10 m sprint time (p = 0.03, d = -0.18) and change of direction time (p = 0.03, d = -0.20) in favour of COMP. In addition, there was a significant, small difference (p = 0.05, d = -0.30) in ellipse area and a small (p = 0.16, d = 0.21) difference in balance time in favour of COMP during a single-leg balance task. There were no significant differences between trials for any of the other balance or jump tests (p > 0.05). The application of compression tights during exercise may offer small benefits to the performance of balance and change of direction tasks, though these benefits are likely within the typical error of measurement for the tests used.